"Ethics, integrity and aptitude" - "Rao, G Subba; Chowdhury, P N Roy" (New Dehli, 2014)
In this second edition, the aptitudes of civil servants and the foundational values of public service in India have been examined in depth, in the light of new researches in the fields of 'neurology' and 'emotional intelligence.' The ethical concerns, dilemmas, and probity issues in governance have been examined in the context of declining moral values, accountability ethics, and galloping corruption in Indian public administration. The chapter on "Moral Philosophies and Philosophers" has been entirely rewritten. Further, a new chapter on "Corporate Social Responsibility and Global Transparency: The Ethical Issues" has been additionally incorporated to highlight the ethical/social responsibility of business and ethical interactions in global politics. The book will provoke civil service aspirants to think and debate the ethical issues woven around the emerging ethos of transparency, new codes of conduct, and work culture. A section of case studies from India will help readers relate theory to a practical understanding of the subject. The book enables readers to identify right attitudes and discover problem-solving approaches when dealing with conflicts. [Subject: India Studies, Ethics, Public Administration
Keywords: Civil Services